2009
DOI: 10.1590/s0100-204x2009000700011
|View full text |Cite
|
Sign up to set email alerts
|

In situ and genetic characterization of Gossypium barbadense populations from the states of Pará and Amapá, Brazil

Abstract: -The objective of this work was to characterize the populations of Gossypium barbadense in the states of Amapá and Pará, Brazil. In situ characterization was conducted through interviews with the owners of the plants and environmental observations. Leaf or petal tissue as well as seed samples were collected for genetic characterization by single sequence repeats markers and for storage in germplasm banks, respectively. The plants were maintained in dooryards and used mainly for medical purposes. The genetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 12 publications
5
21
0
4
Order By: Relevance
“…They have not been previously reported (Menezes et al 2010) and can be used in studies of differentiations of population and, as verified by Petit et al (1998), in the choice of preferred genotypes or populations for preservation. A similar number of exclusive alleles was observed in Gossypium barbadense (Almeida et al 2009), an ancestor species of mocó cotton grown in the Northeastern Brazil. Low oscillations in allelic frequencies were observed between the two states.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…They have not been previously reported (Menezes et al 2010) and can be used in studies of differentiations of population and, as verified by Petit et al (1998), in the choice of preferred genotypes or populations for preservation. A similar number of exclusive alleles was observed in Gossypium barbadense (Almeida et al 2009), an ancestor species of mocó cotton grown in the Northeastern Brazil. Low oscillations in allelic frequencies were observed between the two states.…”
Section: Resultssupporting
confidence: 67%
“…As demonstrated in other works on genetic diversity of cotton population, the use of SSR markers has helped to design conservation strategies (Almeida et al 2009. The high diversity rate inside states and low genetic difference between them has showed that the conservation de cotton plants was given priority in one state in detriment of other.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, the traditional cotton Gossypium barbadense, which used to be cultivated by native South American inhabitants, was classified in different subspecies when the seed from the same boll were adhered to each other, forming the called kidney seeds. This trait is, presumably, controlled by a single locus (Almeida et al, 2009), but for some authors this single trait is not relevant enough to differentiate subspecies, and molecular markers could be used to explain this process. Population genetics has been markedly based on studies using neutral molecular markers, and the obtained genetic structure provides information individuals in a population are more related among themselves than with individuals of other populations.…”
Section: Microrganisms and Pests Associated To Plantsmentioning
confidence: 99%